2013
DOI: 10.1149/05401.0127ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Negative-Bias with Illumination Stress Induced State Creation in Amorphous InGaZnO Thin-Film Transistor

Abstract: Hysteresis of InGaZnO thin-film transistor (IGZO TFT) under negative-bias with illumination stress (NBIS) was investigated using double sweeping gate voltage (VGS) mode. We found that hysteresis of IGZO TFT was significantly enlarged by the NBIS with large negative gate voltage stress. On-current and S value in forward measurements started to show degradation under large-negative VGS stress due to acceptor-like defect creation; on the other hand, transfer curves in reverse measurements shifted to a positive VG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In the case of conventional bottom-gate a-IGZO TFTs, typically an etch-stopper (ES) layer is formed on the channel layer, which protects the backchannel surface from the etching damage induced during formation of source and drain (S/D) electrodes [8]. Silicon oxide (SiO x ), deposited by plasma-enhanced chemical vapor deposition (PE-CVD), is commonly used as an ES layer for a-IGZO TFTs, since the hydrogen content of SiO x is lower than that of hydrogenated silicon nitride (SiN x :H) deposited by PE-CVD [9]- [13]. However, even for the case of the SiO x ES layer deposited by PE-CVD, a certain amount of hydrogen also diffuses from the ES layer into the a-IGZO channel [14].…”
Section: Quantitative Analysis Of the Effect Of Hydrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of conventional bottom-gate a-IGZO TFTs, typically an etch-stopper (ES) layer is formed on the channel layer, which protects the backchannel surface from the etching damage induced during formation of source and drain (S/D) electrodes [8]. Silicon oxide (SiO x ), deposited by plasma-enhanced chemical vapor deposition (PE-CVD), is commonly used as an ES layer for a-IGZO TFTs, since the hydrogen content of SiO x is lower than that of hydrogenated silicon nitride (SiN x :H) deposited by PE-CVD [9]- [13]. However, even for the case of the SiO x ES layer deposited by PE-CVD, a certain amount of hydrogen also diffuses from the ES layer into the a-IGZO channel [14].…”
Section: Quantitative Analysis Of the Effect Of Hydrogenmentioning
confidence: 99%
“…In the case of a-IGZO/SiN x :H stacked film, it has been reported that the amount of hydrogen in the SiN x :H increased when P[SiH 4 ] during the deposition by PE-CVD was increased, and the carrier concentration of the a-IGZO increased as a result of increasing P[SiH 4 ] due to hydrogen diffusion from the SiN x :H into the a-IGZO by thermal annealing [9]. Therefore, we estimated the hydrogen content of the a-IGZO/SiO x stacked films at each P[SiH 4 ] by SIMS.…”
Section: B Quantitative Analysis Of the Relationship Between Tft Promentioning
confidence: 99%
“…Detail NBIS degradation mechanism of the TFT with SiOx-Pa was reported previously. [20][21][22] The NBIS induced degradations were originated from deep subgap states (neutral V O ) existing more than 2 eV away from the conduction band (E C ). Due to photon energy of the blue light, charge state of the V O changed from neutral to positive by emitting trapped electron to E C .…”
Section: Ecs Transactions 67 (1) 41-49 (2015)mentioning
confidence: 99%